The Kembar Mayang Tradition in Marriage, Between Local Wisdom And The Perspective of Islamic Law - Afan, Suhaimi; Al-Am, Maftah Rozani; Pradana, Sandi Yoga (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study examines the Kembar Mayang tradition in Javanese marriage ceremonies as a form of local wisdom imbued with symbolic prayers for marital harmony. The research aims to evaluate this tradition through the lens of Islamic law, specifically determining its classification as ‘urf shahih (valid custom) or a practice contradictory to Islamic principles. Employing a normative juridical approach integrated with socio-cultural analysis, the study focuses on practices within the Kediri region of East Java. Data were gathered through literature reviews and field observations to explore the intersection of cultural values and Islamic jurisprudence. The findings indicate that Kembar Mayang constitutes ‘urf shahih, provided it remains free from polytheistic elements (shirk). It serves as a symbolic medium for prayer, marital sanctity, and social solidarity, representing a successful Islamization of local culture rather than a religious deviation. The study concludes that a contextual approach to Islamic law is essential for accommodating local wisdom while upholding core theological principles. These results advocate for a moderate and inclusive model of Islam that is deeply rooted in indigenous heritage, suggesting that similar traditions across the Indonesian archipelago warrant further scholarly investigation.